Synthesis of Novel Donor-Acceptor Type Molecule Based on Phenothiazine Unit for Organic Light-Emitting Materials - Tang, Zebiao; Sun, Xiaoxia; Shen, Huayin; Yan, Hewei (Asian Journal of Chemistry, 2015)
A novel conjugated organic molecule based on central phenothiazine unit as an electronic donor and aldehyde group termini as an electronic acceptor has been designed and constructed. Optical spectra show that, the absorption and fluorescence spectra of M2 are large red-shifted relative to M1 in both states, however, from solution to the solid state, the absorption maxima and emission maxima of M1 and M2 are in the opposite trends (blue-shift). The fluorescence spectra exhibit that the emission maxima of M1 and M2 which range from 485 nm to 588 nm belong to green light region. As expected, the target compounds should be a promising green light-emitting material for applications in organic light-emitting diodes (OLEDs).